Breathlessness With Pulmonary Metastases: A Multimodal Approach - Brant, Jeannine M. (Harborside Press, 2013)
Case Study  Sarah is a 58-year-old breast cancer survivor, social worker, and health-care administrator at a long-term care facility. She lives with her husband and enjoys gardening and reading. She has two grown children and three grandchildren who live approximately 180 miles away. SECOND CANCER DIAGNOSIS  One morning while showering, Sarah detected a painless quarter-sized lump on her inner thigh. While she thought it was unusual, she felt it would probably go away. One month later, she felt the lump again; she thought that it had grown, so she scheduled a visit with her primary care physician. A CT scan revealed a 6.2-cm soft-tissue mass in the left groin. She was referred to an oncologic surgeon and underwent an excision of the groin mass. Pathology revealed a grade 3 malignant melanoma. She was later tested and found to have BRAF-negative status. Following her recovery from surgery, Sarah was further evaluated with an MRI scan of the brain, which was negative, and a PET scan, which revealed two nodules in the left lung. As Sarah had attended a cancer support group during her breast cancer treatment in the past, she decided to go back to the group when she learned of her melanoma diagnosis. While the treatment options for her lung lesions included interleukin-2, ipilimumab (Yervoy), temozolomide, dacarbazine, a clinical trial, or radiosurgery, Sarah's oncologist felt that ipilimumab or radiosurgery would be the best course of action. She shared with her support group that she was ambivalent about this decision, as she had experienced profound fatigue and nausea with chemotherapy during her past treatment for breast cancer. She eventually opted to undergo stereotactic radiosurgery. DISEASE RECURRENCE  After the radiosurgery, Sarah was followed every 2 months. She complained of shortness of breath about 2 weeks prior to each follow-up visit. Each time her chest x-ray was normal, and she eventually believed that her breathlessness was anxiety-related. Unfortunately, Sarah’s 1-year follow-up exam revealed a 2 cm × 3 cm mass in her left lung, for which she had a surgical wedge resection. Her complaints of shortness of breath increased following the surgery and occurred most often with anxiety, heat, and gardening activities, especially when she needed to bend over. Sarah also complained of a burning "pins and needles" sensation at the surgical chest wall site that was bothersome and would wake her up at night. Sarah met with the nurse practitioner in the symptom management clinic to discuss her concerns. Upon physical examination, observable signs of breathlessness were lacking, and oxygen saturation remained stable at 94%, but Sarah rated her breathlessness as 7 on the 0 to 10 Borg scale. The nurse practitioner prescribed duloxetine to help manage the surgical site neuropathic pain and to assist with anxiety, which in turn could possibly improve Sarah’s breathlessness. Several nonpharmacologic modalities for breathlessness were also recommended: using a fan directed toward her face, working in the garden in the early morning when the weather is cooler, gardening in containers that are at eye level to avoid the need to bend down, and performing relaxation exercises with pursed lip breathing to relieve anxiety-provoked breathlessness. One month later, Sarah reported relief of her anxiety; she stated that the fan directed toward her face helped most when she started to feel "air hungry." She rated her breathlessness at 4/10 on the Borg scale. SECOND RECURRENCE: MULTIPLE PULMONARY NODULES  Sarah’s chest x-rays remained clear for 6 months, but she developed a chronic cough shortly before the 9-month exam. An x-ray revealed several bilateral lung lesions and growth in the area of the previously resected lung nodule. Systemic therapy was recommended, and she underwent two cycles of ipilimumab. Sarah’s cough and breathlessness worsened, she developed colitis, and she decided to stop therapy after the third cycle. In addition, her coughing spells triggered bronchospasms that resulted in severe anxiety, panic attacks, and air hunger. She rated her breathlessness at 10/10 on the Borg scale during these episodes. She found communication difficult due to the cough and began to isolate herself. She continued to attend the support group weekly but had difficulty participating in conversation due to her cough. Sarah was seen in the symptom management clinic every 2 weeks or more often as needed. No acute distress was present at the beginning of each visit, but when Sarah began to talk about her symptoms and fear of dying, her shortness of breath and anxiety increased. The symptom management nurse practitioner treated the suspected underlying cause of the breathlessness and prescribed oral lorazepam (0.5 to 1 mg every 6 hours) for anxiety and codeine cough syrup for the cough. Opioids were initiated for chest wall pain and to control the breathlessness. Controlled-release oxycodone was started at 10 mg every 12 hours with a breakthrough pain (BTP) dose of 5 mg every 2 hours as needed for breathlessness or pain. Sarah noted improvement in her symptoms and reported a Borg scale rating of 5/10. Oxygen therapy was attempted, but subjective improvement in Sarah’s breathlessness was lacking. END OF LIFE  Sarah’s disease progressed to the liver, and she began experiencing more notable signs of breathlessness: nasal flaring, tachycardia, and restlessness. Opioid doses were titrated over the course of 3 months to oxycodone (40 mg every 12 hours) with a BTP dose of 10 to 15 mg every 2 hours as needed, but her breathlessness caused significant distress, which she rated 8/10. The oxycodone was rotated to IV morphine continuous infusion with patient-controlled analgesia (PCA) that was delivered through her implantable port. This combination allowed Sarah to depress the PCA as needed and achieve immediate control of her dyspneic episodes. Oral lorazepam was also continued as needed. Sarah’s daughter moved home to take care of her mother, and hospice became involved for end-of-life care. As Sarah became less responsive, nurses maintained doses of morphine for control of pain and breathlessness and used a respiratory distress observation scale to assess for breathlessness since Sarah could no longer self-report. A bolus PCA dose of morphine was administered by Sarah’s daughter if her mother appeared to be in distress. Sarah died peacefully in her home without signs of distress.